(untitled) - Hjortsø,Martin A (New York, 2006)
The process of separating and classifying individual cell populations is one of the most critical and difficult tasks faced by engineers and scientists when creating biomaterials. To this end, many engineers and researchers use population balance modeling to achieve accurate counts of any population. This resource focuses on overcoming obstacles to help researchers and scientists build computer models that accurately approximate properties and classification of different populations.
Keywords: Biological models,Cell division,Biomedical Engineering,Mô hình sinh vật học